Sistem Informasi Pencarian Alamat Kampus UBSI Berbasis Android dengan Metode Location Based Service - Cepi Cahyadi; Mety Titin Herawaty (STMIK IKMI Cirebon, 2019)
Searching the address of the campus of Bina Sarana Informatika University which has PSDKU, almost 29 campuses outside the main campus spread throughout Indonesia at this time can only be through official documents, brochures and on calendars made by the campus and there are also installed on the wall in the environment campus. The current address search process will be developed into a digital information system in the form of an Android-based Mobile technology. This technology is made using the android studio application and MySQL database. With the Location Based Service (LBS) and GPS technology methods, the user will be given location information and routes to the UBSI campus that is addressed easily. The purpose of planning this system is to provide convenience in the delivery of information on address searches of the campus of the University of Bina Sarana Informatika (UBSI) widely for mobile users that can be accessed via the internet. Through the development of this system, access to information can be done anytime and anywhere without having to deal directly with existing resources.